An approach to the analysis of the impedance spectra of solid oxide fuel cell using the DRT technique. (10th March 2021) - Osinkin, D.A.
Highlights: The analysis of the impedance spectra of a SOFC by the DRT technique was performed. The influence of gas phase composition on electrode performance was determined. The DRT method can qualitatively determine the activity of the electrodes of SOFC. Abstract: Determination of the polarization resistance of the anode and cathode in a solid oxide fuel cell (SOFC) with a thin-film electrolyte is a complicated task due to the difficulty of the manufacturing the reference electrode. In this case, only the total polarization resistance of the electrodes is available for analysis. When the relaxation times of the electrode processes are close, the separation of the electrode reactions, in most cases, is impossible by the conventional nonlinear least-squares method due to а several reaction processes in anode and cathode. In this paper, using a fuel cell with a supporting cathode as an example it is shown that the distribution of relaxation times (DRT) technique for the analysis of the impedance spectra of the fuel cell can be used to determine the polarization resistance of the cathode and anode. This becomes possible at comparing and analyzing the DRT functions obtained by varying the composition of gas mixtures at the cathode and anode of the fuel cell, using an electrocatalyst to accelerate the cathode reaction as well as comparing the DRT functions of the fuel cell with the supporting cathode to the DRT functions of cells with supporting electrolyte and symmetric electrodes.